PELATIHAN KADER POSYANDU LANSIA DALAM SKRINING KESEHATAN LANSIA DI DESA PADANG LUAS - Handayani, Handayani; Sembiring, Ligat Pribadi; Indriani, Haidatul; Alfarez, Muhammad Rendi; Garneta, Shafira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The aging process in the elderly is characterized by a decline in physical and psychological abilities as well as an increased risk of disease that can lead to death. The high proportion of morbidity and disability in the elderly group can result in an increase in the need for health services. One form of health service for the elderly is the elderly posyandu..The implementation of posyandu activities for the elderly is carried out by health workers and cadres. Cadres often encounter obstacles in implementing elderly posyandu activities, one of which is the lack of access to information regarding guidelines for properly serving 5 elderly posyandu tables. This service aims to provide guidance and training on how to properly serve 5 posyandu tables for the elderly according to national guidelines. The community service activities carried out have shown results that meet the success criteria. After the training, cadres showed increased knowledge about elderly health and had a positive attitude about the need for elderly posyandu. Cadres are also more skilled in carrying on examining the elderly’s health condition